Real Time Product Feedback Review and Analysis Using Apache Technologies and NOSQL Database (International Journal of Engineering and Computer Science, 2017)
Whenever a feedback system comes into mind, it’s always a demand of the e-commerce organizations to get the customer feedbacks in real time and to build some strong dashboards on top of these feedbacks/ratings. So that they can easily know the performance of any product at any point of time as well as they could able to take a decision, on what to do with the products those are getting very poor feedbacks. Which will result in a minimum impact on the tangible and intangible assets of the organizations. For achieving the above goal it is very necessary for these organizations to adopt the right tool and implement the required environment which can deal with the real time big data ingestion, enrichment, indexing and have the power to perform simple as well as complex analysis algorithm on the stored data. In this paper, we have collected Amazon Product Ratings for doing analysis and used Apache NiFi for ingesting real-time data into Apache Solr and have taken help of Banana Dashboard to show the real time analysis results in the form of attractive and user-friendly dashboards.